Analysis of EGFR signaling pathway; miRNAs and inflammatory biomarkers in a high-risk oral cancer population in Pakistan - An exploratory study - Namrah Anwar; Shahid Pervez; Tariq Moatter; Mitchell Stark; Qurratulain Chundriger; Tazeen Saeed Ali; Sohail Awan; Annika Antonsson (PLoS ONE, 2026)
Oral cancer has high morbidity rates in the Asian region, specifically Pakistan. However, little insight is available regarding the molecular pathogenesis and inflammatory biomarkers of this preventable cancer. This study determined the association of EGFR, NFκB, COX-2, and miRNAs expression with the chewing habits and high-risk human papillomavirus (HR-HPV) infection in oral cancer patients. Formalin-fixed paraffin-embedded blocks (FFPE) (n = 50) were analyzed for transcriptional expression of EGFR, NFκB, and COX-2 by qPCR and COX-2 protein expression was checked by immunohistochemistry (IHC). Array profiling of ~2500 miRNAs was performed on nine samples, and five miRNAs were selected for validation from this profiling data. Appropriate statistical tests were applied to check the association of EGFR., NFκB, COX-2, and miRNAs with chewing and HR-HPV status, (p < 0.05 and 95% CI). Of the 50 samples, transcriptional expression of EGFR was observed in 13 (26%), NFκB in 11 (22%), and COX-2 in 17 (34%) samples, and the majority were chewers. EGFR and COX-2 expression was significantly associated with chewing gutka (the most carcinogenic form of chewing substance). A total of 281 miRNAs were dysregulated in miRNA profiling, and in validation, miR-222-3p was significantly downregulated in chewers expressing EGFR, NFκB, and COX-2 compared to non-chewers (p < 0.05). HR-HPV positivity was not correlated with miRNAs. This study suggests a significant association of chewing habits with EGFR and COX-2 expression. In addition, the molecular pathogenesis of OSCC suggests the substantial interplay of NFκB, COX-2, EGFR and miRNAs in chronic chewers, irrespective of HR-HPV involvement.